Sri Ksetra Museum Collection Inventory. - Galloway, Charlotte. (Beyond Boundaries Series, 2022)
Beyond Boundaries: Religion, Region, Language and the State is a research initiative hosted by the British Museum and the British Library in London. Moving beyond geographical, chronological, disciplinary and historiographical boundaries, the books in this series explore the interactions of India and her neighbors from late antiquity to the close of the medieval.